Employee Motivation and Job Performance in the Public Service of Uganda: The Case of the Office of the Director of Public Prosecutions - Batson, Baguma (Kabale University, 2022)
The purpose of this study was to assess employee motivation and performance in the public service, a case study of the Office of the Director Public Prosecution of Uganda. The objectives were: to establish the levels of intrinsic motivation in the ODPP; to establish the level of extrinsic motivation in ODPP; and, to examine the factors that determine employee motivation on the employee performance in the ODPP. The study used a target population of 472 selected ODPP staff as well as some officials from sister institutions such as Judiciary, Police and Probation. A total of 216 respondents was reached and selected using Krejcie and Morgan (1970) sample size formula table. A descriptive research design was employed with both quantitative and qualitative approaches as simple random sampling was employed to get the respondents. Data were analysed using descriptive statistics and bivariate statistics. The results showed that there was a strong and positive relationship between motivation and employee performance in ODPP; that 90% of those who mentioned monetary incentives either strongly agreed (65.6%) that this affects their performance which indicated that motivation improves performance and, that despite the low monetary incentives 20.6%, promotion at work places 40.3 %, continued job training at 58.5% and good relationship with supervisors 82% was one of the ways in which employees were motivated at the ODPP. The study concluded that overall, ODPP is expected to provide an appropriate salary for the employees as promised by the government; the current salary is considered disproportional compared with other institutions in the justice law and order sector; limited career path in the ODPP; ODPP still has to handle appropriation of their rewarding recognition for employees’ performance in the form of financial incentives, a recognition certificate, direct verbal compliments; there is big criticism regarding work-life balance factors. Most employees argued that the workload and working hours are too high. The study recommends that the ODPP needs to consider practical measures to improve on the motivation of its employees and enhance performance through Salary policy review for overtime rate for all employees; there is a need for a workload and job description review. The adjustment on workload is required in order to improve the work-life balance factor; that a clear procedure of performance evaluation process be instituted and reward/recognition factor should be considered good; ODPP needs to maintain and improve it in order to increase the motivation level of the employees in order to enhance their performance. Because productivity and performance of most organizations depend on how readily available and committed the workforce is, the absence or low level of factors of motivation effects employee’s motivation and hence negatively affects performance.